KUALITAS AIR DANAU BUYAN DAN TAMBLINGAN MENURUT PARAMETER FISIKA, KIMIA DAN BIOLOGI - Ni Made Hegard Sukmawati (Scopus ID: 57189732715) (Warmadewa University, 2020)
Buyan Lake and Tamblingan Lake are known as twin lakes in Bali which serve not only as water sources for agriculture and households, but also as tourist destinations. Infrastructure development and the up-surge of tourism activities potentially increase the contamination of lake water in Bali. The aim of this study was to investigate the quality of water in Buyan Lake and Tamblingan Lake based on physical, chemical, and biological parameters. Five sampling sites (stations) were purposively chosen in each of the lakes. Physical parameters (temperature and total dissolved solids) and chemical parameters (dissolve oxygen, biochemical oxygen demand, chemical oxygen demand, pH, phosphate, ammonia, nitrate, and heavy metal) were measured from each station. Coliform and fecal coli were also tested to assess biological contamination. The level of contamination were compared to the Bali Governor Regulation no 16 Year 2016 on Water Quality Manage-ment and Pollution Control. Among 14 parameters being measured on Buyan Lake water samples, two of them did not meet the standard water quality 1: BOD (2.19 ± 0.64 mg/l) and COD (49.18 ± 28.70 mg/l). While, wa-ter samples from Tamblingan Lake had 3 parameters above the standard water quality 1: COD (62.92 ± 17.93 mg/l), phosphate (0.23 ± 0.19 mg/l), and coliform (3319 ± 7090 MPN/100 ml). In general, water samples from both lakes did not meet the criteria for potable water neither for recreational activities. High COD in both lakes indicated high organic contaminants.